Effect Of Isradipine On MES And Picrotoxin Induced Convulsion - DEVI.K; KAVIMANI.S (International Journal of Pharma and Bio Sciences, 2010)
Calcium channel blockers are used as effective agent in various disorders of cardiovascular system such as angina, hypertension and arrythmiasis. Calcium ions play a central role in the control of neuronal excitability. Therefore this study was designed to find out the effect of Isradipine on MES and Picrotoxin induced convulsion. The maximal seizure pattern was induced in animals by giving an alternating current of 150 mA for 0.2 sec while tonic – clonic seizure with 2 mg/kg; ip of Picrotoxin. Isradipine (80µg/kg; ip), Phenytoin (25mg/kg; ip), Diazepam (10mg/kg; ip), Phenytoin + Isradipine, and Diazepam + Isradipine were administered 30 min before electrical/chemical induction of convulsion. The ability of test group to abolish/reduce tonic hind limb extensor component in MES group and delay in onset of jerky movement & death time in Picrotoxin induced group was measured as antiepileptic criteria. Isradipine produced significant reduction in the extensor phase when compared with control and also it potentiated the abolition when compared with Phenytoin in MES induced convulsion. Similarly Isradipine delay the onset of action and time of death in Picrotoxin induced convulsion with 100% recovery of animals when combined with Diazepam. The anticonvulsant property may be by blockade of voltage dependent calcium channels by which calcium ions influx is blocked to stop the sequence of events leading to both the spread of epileptic discharge, cell damage and death.